Covid-19 - Sata, Robert (Journal of comparative politics, 2025)
We examine how pandemic crisis management has affected public support in the democratic backsliding members of the EU – Poland and Hungary. We claim the first, immediate effect of the pandemic is to “rally around flag” but since populist illiberal governments adopt authoritarian measures, the ongoing pandemic brings to the fore populists' failure/ineffective crisis management, and thus public dissatisfaction should erode support for the incumbents. Relying on original survey data collected during the Covid-19 pandemic, we test several possible sources of dissatisfaction: the state of the healthcare; the economy; corruption and abuse of power; and distorted communication/false information on the crisis. Citizens dissatisfied with governing populist parties’ performance should be willing to punish the “guilty” party withdrawing their support, yet we find partisan preferences affect government accountability evaluations and leave supporters immune to policy negative effects. Comparing Hungary to Poland, we see the more polarized society is, the more likely extraordinary circumstances will only reinforce divisions in society and strengthen incumbents.
Keywords: accountability; antidemokratičnost; autocratization; avtokratizacija; Avtoritarizem; Covid-19; democratic backsliding; demokratično nazadovanje; javna podpora; javno zdravje; Krize; odgovornost; partisanship; Populizem; public health; public support; strankarstvo